Improvisation? Just do it! Report of the activities in the field of improvisation at the Royal conservatoire The Hague - Prchal, Martin; Reinink, Adriaan (The Hague Royal conservatoire publication, 2012)
The Royal Conservatoire has made a publication about the improvisation projects that the Royal Conservatoire organised from 2010 to 2012.